2007
DOI: 10.1007/s00221-007-0957-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereo vision enhances the learning of a catching skill

Abstract: The aim of this study was to investigate the contribution of stereo vision to the acquisition of a natural interception task. Poor catchers with good (N = 8; Stereo+) and weak (N = 6; Stereo¡) stereo vision participated in an intensive training program spread over 2 weeks, during which they caught over 1,400 tennis balls in a pre-postretention design. While the Stereo+ group improved from a catching percentage of 18% to 59%, catchers in the Stereo¡ group did not signiWcantly improve (from 10 to 31%), this prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 14 publications
(19 reference statements)
3
40
0
1
Order By: Relevance
“…Initial learning occurred with 20 minutes of training; however, the performance gap remained constant between these students and those with normal depth perception. Mazyn et al 17 found that a group with a significant lack of stereopsis did not improve with training during a catching task. However, catching a ball is not comparable to performing cataract surgery, and stereoacuity is only 1 factor that determines surgical skills.…”
Section: Discussionmentioning
confidence: 98%
“…Initial learning occurred with 20 minutes of training; however, the performance gap remained constant between these students and those with normal depth perception. Mazyn et al 17 found that a group with a significant lack of stereopsis did not improve with training during a catching task. However, catching a ball is not comparable to performing cataract surgery, and stereoacuity is only 1 factor that determines surgical skills.…”
Section: Discussionmentioning
confidence: 98%
“…24 Several additional studies of adults have examined the effects of poor stereopsis on fine motor skills. Subjects with poor stereopsis were found to have greater difficulty than controls in catching a tennis ball 25,26 and in performing a manipulation involving a wire loop and peg insertion. 27 Monocular occlusion of otherwise normal subjects has also been shown to have a detrimental effect on fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, amblyopia has been found to significantly reduce speed and dexterity of prehension ( particularly in children with a history of strabismus), 3 without diminishing accuracy and control. [3][4][5] Evidence also has come to light that amblyopic subjects' binocular reading speed is significantly slower than that of normal subjects, despite the amblyopic subjects having the same levels of binocular visual acuity and reading acuity as the normal subjects, 6 and also that amblyopic individuals have poorer depth discrimination from motion parallax than normal subjects. 7 However, it seems useful to consider possible reasons for the 2 cohort study findings.…”
mentioning
confidence: 92%